Analisis pengaruh budaya organisasi dan kepuasan kerja terhadap kinerja karyawan bagian marketing Bank Panin Pekanbaru - Dani Rizki Pratama; Samsir '; Dewita Suryati Ningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to analyze the effect in partial and simultaneous of variable organizational culture and job satisfaction to employee performance marketing section of Bank Panin Pekanbaru. Study using purposive sampling and stratified sampling by giving questionnaire to the respondents. Analysis of the data using qualitative methods and quantitative methods by SPSS (Statistical Package for Social Science) version 20.0. The result showed organizational culture and job satisfaction to employee performance marketing section of Bank Panin Pekanbaru and the effect in partial and simultaneously. The coefficient of determination (R2) equal to 69.50% and the remaining 30.5% is influenced by other factors not examined in this study. Organizational culture has a stronger influence on employee performance. So good organizational culture of a company and job satisfaction of employees created by employee will improve employee performance marketing section of Bank Panin Pekanbaru.Keywords: Organizational Culture, Job Satisfaction, Employee Performance.